Analysis of the profitability of solar energy implementation as a determinant of sustainable economy - Zdravković, Vladimir; Popović, Zoran; Kotarac, Đorđe (Industrija, 2025)
At the beginning of the new millennium, the consumption of the natural resources and the size of the worlds’ population become inversely correlated. The motive of this research is to confirm the influence of solar energy in the direction of implementing the strategy of sustainable development of countries. The aim of research is to calculate the consumption share of the household budget and the profitability of investing in the installation of renewable resources for electricity supply in Serbia. The results of the research confirm a significant reduction of the funds allocated for the supply of electricity through the installation of solar panels, while ensuring the return on investment in the extrapolation period. The research concludes that the use of renewable energy sources is a key determinant of sustainable development and protection of the natural environment. Namely, the transition to renewable energy sources provides financial and environmental benefits for the entire society.